Adhesive sheet and method for peeling adhesive sheet

By using multifunctional monomers and thermally reactive compounds in the adhesive layer, thermal curing is achieved, and the problem of difficult peeling of thermosetting adhesives at high temperatures is solved, and stable peelability and low gas release effect is achieved.

CN119546718APending Publication Date: 2025-02-28NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380051380.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

It is difficult for existing thermosetting adhesives to achieve stable peelability after heating at high temperatures, which easily leads to adsorption of the adhesive on the surface of the adhered, increasing the peeling force and possibly producing residual glue.

Method used

By including a multifunctional monomer in the adhesive layer, the heat-reactive compound is used to react during heating, and thermal curing is achieved, thereby achieving heat-easy peelability. At the same time, the content and molecular weight of the multifunctional monomer are controlled to ensure that release gas is not easily generated during heating.

Benefits of technology

It has achieved stable peelability under high temperature conditions, reduces adsorption of adhesive onto the adherend, reduces the peeling force and the generation of residual glue, and limits the amount of gas released.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119546718A_ABST
    Figure CN119546718A_ABST
Patent Text Reader

Abstract

Provided is an adhesive sheet having heat-peelability and reduced release gas. Provided is an adhesive sheet having an adhesive layer. The adhesive layer contains a polymer and a polyfunctional monomer having a weight loss rate of 1% or less when heated at 180 DEG C based on TGA. The content of the polyfunctional monomer is 30 parts by weight or more with respect to 100 parts by weight of the polymer. The adhesive sheet has a peel strength with respect to a glass plate of 1.0 N / 20 mm or less after being heated at 180 DEG C for 1 hour.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet and a method for peeling the adhesive sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2022-120902 filed on July 28, 2022, the entire contents of which are incorporated herein by reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives. The same applies hereinafter) have the following properties: they are in a soft solid (viscoelastic) state in a temperature range near room temperature, and are easily adhered to an adherend by pressure. In view of the excellent operability of pasting to an adherend, adhesives are widely used in various fields in the form of an adhesive sheet with an adhesive layer on a support, or in the form of an adhesive sheet without a support. Among such adhesives, there are adhesives that are used by adhering to an adherend and are removed from the adherend after the purpose of the bonding is completed. As prior art documents disclosing such prior art, Patent Documents 1 to 4 can be cited. Patent Documents 1 to 4 disclose thermosetting adhesives.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-29105

[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-204617

[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-56101

[0009] Patent Document 4: Japanese Patent Application Publication No. 10-209087

[0010] Non-patent literature

[0011] Non-patent literature 1: Simone Napolitano, 'Irreversible adsorption of polymer melts and nanoconfinement effects', SoftMatter, 2020, 16, pp. 5348-5365

[0012] Non-Patent Document 2: Ben O'Shaughnessy and Dimitrios Vavylonis, 'Non-Equilibrium in Adsorbed Polymer Layers', J. Phys.: Condens. Matter, 17, 2005, pp. R63-99 Summary of the invention

[0013] Problems to be solved by the invention

[0014] For adhesives used for peeling and removing from adherends, it is required to have good adhesion during adhesion to the adherend and to be easily peeled from the adherend after the purpose of adhesion is completed. For example, for adhesives suitable for adherends to be treated by heat, it is expected to have easy peelability that can be easily peeled from the adherend after being heated in a state of being adhered to the adherend. However, if adherends such as glass and metal are heated at high temperature in a state of being adhered with an adhesive, there is a risk of undesirable conditions such as the adhesive being adsorbed on the surface of the adherend, thereby increasing the peeling force (heavy peeling), reducing the peeling property, or generating residual adhesive. In this regard, see the various polymers described in non-patent documents 1 to 2 that have adsorption force by heating. For example, in the case of thermosetting adhesives such as those described in patent documents 1 to 4, it is difficult to make the curing of the adhesive during high-temperature heating appear before the adsorption of the adhesive to the adherend, and the peeling force reduction and peeling force increase suppression based on the curing of the adhesive cannot be obtained, and stable easy peelability cannot be obtained after high-temperature heating.

[0015] Based on such background, the inventor of the present application focuses on thermosetting adhesives, and has carried out research and development based on design concepts different from the past. As a result, an adhesive that is attached to the adherend and has easy peelability (heating easy peelability) after being heated at high temperature is successfully obtained. As for this heating easy peelability, it is usually easy to peel after the heating treatment with increased peeling force, so it is also called heat-resistant easy peelability. The above-mentioned thermosetting adhesive contains thermo-reactive compounds such as multifunctional monomers, and the thermo-reactive compounds are reacted when heated to perform heat curing, and the heating easy peelability is exerted. However, through the research of the inventor of the present application, it has been found that it is difficult to make the thermo-reactive compounds such as multifunctional monomers contained in the adhesive react completely, and a certain amount of unreacted substances will remain in the adhesive, and become the so-called released gas (released gas) when heated. In addition, among the thermo-reactive compounds, there are also substances that generate low molecular weight substances (decomposed products) in the reaction when heated, which will also become the cause of released gas. Such released gas will become the cause of contamination of the adherend, so it is not expected. In addition, the released gas may cause adverse conditions depending on the application and application site of the adhesive, and is therefore undesirable. For example, in the application of temporary fixing of materials using pressure difference, adhesion of adhesive sheets, and processing of adherends under vacuum, the adhesive is used in a vacuum or reduced pressure environment. In these applications, if the amount of released gas from the adhesive is large, the vacuum degree is reduced, which may cause adverse conditions.

[0016] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive sheet that has heat-removability and reduces outgassing. Another related object of the present invention is to provide a method for removing the pressure-sensitive adhesive sheet from an adherend.

[0017] Means for solving problems

[0018] According to the present specification, an adhesive sheet having an adhesive layer is provided. The adhesive layer contains a polymer and a multifunctional monomer having a weight loss rate of 1% or less when reaching 180°C in a thermogravimetric analysis (TGA) under a temperature increase condition of 10°C / minute. The content of the multifunctional monomer is 30 parts by weight or more relative to 100 parts by weight of the polymer. In addition, the peel strength after heating of the adhesive sheet to a glass plate measured after heating at 180°C for 1 hour is 1.0N / 20mm or less. The peel strength after heating of the adhesive sheet is 1.0N / 20mm or less, so it has easy peelability by heating. In addition, the adhesive layer contains a multifunctional monomer in an amount greater than a prescribed amount for easy peelability by heating, but the multifunctional monomer used has heat resistance such that the weight loss rate at 180°C is less than 1% based on TGA, so it is not easy to generate released gas when heated. Therefore, according to the above-mentioned configuration, an adhesive sheet that takes into account both easy peelability by heating and reduced released gas is realized.

[0019] In some preferred embodiments, the molecular weight of the polyfunctional monomer is greater than or equal to 250. As the polyfunctional monomer having the heat resistance, a compound having a molecular weight of greater than or equal to 250 is preferably used.

[0020] In some preferred embodiments, the multifunctional monomer has 4 or more ethylenically unsaturated groups. By using a multifunctional monomer having 4 or more ethylenically unsaturated groups (functional groups), it is possible to obtain easy peeling by heating with a relatively small amount of use. This method reduces the amount of released gas from the multifunctional monomer, which is advantageous.

[0021] In some embodiments, the adhesive layer includes a multifunctional acrylate monomer as the multifunctional monomer. The effect of the technology disclosed herein is preferably achieved by using a multifunctional acrylate monomer as the multifunctional monomer. For example, by combining an acrylic polymer and a multifunctional acrylate monomer, the desired effect can be ideally achieved.

[0022] In some preferred embodiments, the adhesive layer includes an acrylic polymer as the polymer. The technology disclosed herein is preferably implemented using an acrylic polymer.

[0023] In some embodiments, the adhesive layer further comprises a thermal polymerization initiator. By including the thermal polymerization initiator in the adhesive layer, when heated, the multifunctional monomer reacts with the thermal polymerization initiator and the adhesive is thermally cured. Thus, it is possible to achieve ideal heat-resistant peelability.

[0024] In some preferred embodiments, the content of the thermal polymerization initiator in the adhesive layer is less than 1.2 parts by weight relative to 100 parts by weight of the polymer. According to the technology disclosed herein, the amount of the thermal polymerization initiator used is limited as described above, thereby suppressing the generation of released gas from the thermal polymerization initiator and achieving easy peelability by heating.

[0025] In addition, according to the present specification, a method for peeling an adhesive sheet adhered to an adherend from the adherend is provided. The method includes: after subjecting an adherend to which any adhesive sheet disclosed herein is adhered to a heat treatment at a temperature higher than 150°C, the step of peeling the adhesive sheet from the adherend. The adhesive sheet disclosed herein has heat-resistant peelability (heat-resistant peelability), so it can be easily peeled from the adherend even after being exposed to heating exceeding 150°C. In addition, the release of gas from the adhesive sheet is reduced, so the adhesive sheet and the peeling method can be used with fewer restrictions in various uses including uses in which the release of gas is not desired. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] [ Figure 1] is a cross-sectional view schematically showing an example of a form of an adhesive sheet. DETAILED DESCRIPTION

[0027] The following describes a suitable embodiment of the present invention. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of filing the application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0028] It should be noted that, in the following drawings, the same reference numerals are sometimes used to mark components and parts that play the same role for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are illustrated for the purpose of clearly describing the present invention, and do not necessarily accurately represent the size or reduction ratio of the product actually provided.

[0029] In this specification, the so-called "base polymer" of the adhesive refers to the main component of the rubber polymer contained in the adhesive. The so-called rubber polymer refers to a polymer that exhibits rubber elasticity in a temperature range near room temperature. In addition, in this specification, the so-called "main component" refers to a component contained in an amount exceeding 50% by weight unless otherwise specified.

[0030] In this specification, the term "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. The acrylic polymer in this specification is defined as a polymer containing monomer units derived from an acrylic monomer.

[0031] In addition, in this specification, the so-called "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, the so-called "(meth)acryloyl group" refers to both acryloyl and methacryloyl groups. Therefore, the concept of acrylic monomers mentioned here may include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, in this specification, respectively, the so-called "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid, and the so-called "(meth)acrylate" refers to both acrylate and methacrylate. The same is true for other similar terms.

[0032] In addition, in this specification, "weight" can be replaced by "mass". For example, "weight %" can be replaced by "mass %", and "weight parts" can be replaced by "mass parts".

[0033] <Adhesive Sheet>

[0034] The adhesive sheet disclosed herein comprises an adhesive layer and is constituted. The adhesive sheet can be an adhesive sheet with a substrate having the form of the above-mentioned adhesive layer on one or both sides of a non-peelable substrate (supporting substrate), or can be an adhesive sheet without a substrate (that is, an adhesive sheet without a non-peelable substrate. Typically, an adhesive sheet formed by an adhesive layer) in which the above-mentioned adhesive layer is retained in the form of a release liner. In the concept of the adhesive sheet mentioned herein, substances referred to as adhesive tapes, adhesive labels, adhesive films, etc. can be included. The adhesive sheet disclosed herein can be in a roll or in a monolithic form. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0035] The cross-sectional structure of the adhesive sheet is shown in Figure 1 .like Figure 1 As shown, the adhesive sheet 1 has an adhesive surface 1A, and is a single-sided adhesive sheet in which an adhesive layer 20 is provided on a surface 10A on one side of a sheet-like substrate layer (support substrate) 10. The adhesive sheet 1 is used in a manner that the surface 20A of the adhesive layer 20 as its adhesive surface 1A is pasted to an adherend. The back surface 10B of the substrate layer 10 (the surface on the opposite side to the surface 10A on one side) is also the back surface 1B of the adhesive sheet 1, constituting the outer surface of the adhesive sheet 1. The adhesive sheet 1 before use (i.e., before adhering to the adherend) can be a form of an adhesive sheet 50 with a release liner in which the adhesive surface 1A is protected by a release liner 30 on the adhesive layer 20 side as a release surface. Alternatively, it can also be a form of an adhesive sheet in which the surface (back surface) 10B on the other side of the substrate layer 10 becomes a release surface, and the adhesive layer 20 is abutted against the back surface by the adhesive sheet 1 being wound into a roll so that the surface (adhesive surface 1A) is protected.

[0036] <Characteristics of adhesive sheets>

[0037] (Peel strength after heating F1)

[0038] The adhesive sheet disclosed herein has a peel strength F1 to a glass plate measured after heating at 180°C for 1 hour (peel strength to a glass plate after heating) of 1.0 N / 20 mm or less. The adhesive sheet showing the peel strength F1 to a glass plate after heating has heat-resistant peelability after heat treatment. From the viewpoint of peelability, it is appropriate that the peel strength F1 to a glass plate after heating is 0.9 N / 20 mm or less, preferably 0.8 N / 20 mm or less, more preferably 0.6 N / 20 mm or less, further preferably 0.5 N / 20 mm or less, and may be 0.4 N / 20 mm or less, or 0.3 N / 20 mm or less. The lower limit of the peel strength F1 to a glass plate after heating may be 0.0 N / 20 mm, or may be 0.01 N / 20 mm or more (for example, 0.1 N / 20 mm or more). The above-mentioned peel strength F1 to the glass plate after heating specifically refers to the peel strength to the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min in an environment of 23° C. after a heat treatment at 180° C. for 1 hour in a state of being attached to an adherend. The above-mentioned peel strength F1 to the glass plate after heating is more specifically measured by the method described in the examples described later.

[0039] (Initial peel strength F0)

[0040] Although not particularly limited, it is appropriate that the initial peel strength (initial peel strength to glass plate) F0 of the adhesive sheet to the glass plate is 0.5N / 20mm or more, may be 0.8N / 20mm or more, and is preferably greater than 1.0N / 20mm. The adhesive sheet showing the above-mentioned initial peel strength F0 to the glass plate can exhibit good adhesion to the adherend. From the viewpoint of adhesion, the above-mentioned initial peel strength F0 to the glass plate may be 1.2N / 20mm or more, 1.5N / 20mm or more, 1.8N / 20mm or more, or 2.0N / 20mm or more. The upper limit of the initial peel strength F0 to the glass plate can be appropriately set according to the required adhesion, and is therefore not limited to a specific range, for example, it may be less than about 20N / 20mm, less than about 10N / 20mm, less than about 5N / 20mm, or less than about 3N / 20mm. The initial peel strength F0 against a glass plate is specifically measured at a peeling angle of 180 degrees and a speed of 300 mm / min at 23° C. The initial peel strength F0 against a glass plate is more specifically measured by the method described in the examples described below.

[0041] (F1 / F0)

[0042] In some embodiments, the peel strength F1 [N / 20mm] of the adhesive sheet after heating is less than 100% of the initial peel strength F0. In other words, the ratio (F1 / F0) of the adhesive sheet is less than 1. The above ratio (F1 / F0) can be less than 0.8, and it is appropriate to be less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and can also be less than 0.15. The adhesive sheet that meets this characteristic is well bonded to the adherend and can exhibit good heating peelability and heat-resistant peelability when peeled after heat treatment. The lower limit of the above ratio (F1 / F0) is not particularly limited, for example, it can also be about 0.01 or more.

[0043] (Peel strength after 30 minutes heating)

[0044] Although not particularly limited, it is preferred that the peel strength of the adhesive sheet to the glass plate measured after heating at 180°C for 30 minutes (peel strength to the glass plate after 30 minutes of heating) is 1.0N / 20mm or less. The adhesive sheet showing the peel strength to the glass plate after 30 minutes of heating has heating-easy peelability, and can be easily peeled off by heat curing by short-term high-temperature heating, and can be easily peeled off from the adherend. From the viewpoint of peelability, it is appropriate that the peel strength to the glass plate after 30 minutes of heating is 0.9N / 20mm or less, preferably 0.8N / 20mm or less, more preferably 0.6N / 20mm or less, further preferably 0.5N / 20mm or less, can be 0.4N / 20mm or less, and can also be 0.3N / 20mm or less. The lower limit of the peel strength to the glass plate after 30 minutes of heating can be 0.0N / 20mm, or can be 0.01N / 20mm or more (for example, 0.1N / 20mm or more). The above-mentioned peel strength to a glass plate after heating for 30 minutes specifically refers to the peel strength to a glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min in an environment of 23°C after heating at 180°C for 30 minutes in a state of being attached to an adherend. More specifically, the above-mentioned peel strength to a glass plate after heating for 30 minutes is measured in the same manner as the above-mentioned peel strength after heating F1 except that the heating treatment conditions are changed to 180°C for 30 minutes.

[0045] (Peel strength after storage FS0)

[0046] Although not particularly limited, in some embodiments, for the adhesive sheet, the peel strength to the glass plate (peel strength to the glass plate after storage) FS0 measured using the adhesive sheet after storage at 60°C for 7 days is appropriately 0.5N / 20mm or more, and may be 0.8N / 20mm or more, and preferably greater than 1.0N / 20mm. For the adhesive sheet showing the above-mentioned peel strength to the glass plate FS0 after storage, good adhesion can be exerted after storage regardless of long-term storage, temperature conditions during storage, etc. From the perspective of adhesion, the above-mentioned peel strength to the glass plate FS0 after storage may be 1.2N / 20mm or more, 1.5N / 20mm or more, or 1.8N / 20mm or more. The upper limit of the peel strength to the glass plate FS0 after storage may be, for example, about 20N / 20mm or less, about 10N / 20mm or less, about 5N / 20mm or less, or about 3N / 20mm or less. The post-storage peel strength FS0 to a glass plate specifically refers to the peel strength to a glass plate measured at a peel angle of 180 degrees and a speed of 300 mm / min at 23° C. after the adhesive sheet has been stored at 60° C. for 7 days.

[0047] More specifically, the post-storage peel strength FS0 of the glass plate is measured by the following method.

[0048] The adhesive sheet was stored at 60°C for 7 days. The adhesive sheet after storage was used to prepare an evaluation sample by the method described in the determination of the initial peel strength F0. Then, the peel strength (peel strength to the glass plate after storage) FS0 [N / 20 mm width) was measured by the same method as the method described in the initial peel strength F0. The adherend, tensile testing machine, and other matters were the same as those for the determination of the initial peel strength F0.

[0049] (Peel strength after storage / heating FS1)

[0050] Although not particularly limited, in some embodiments, for an adhesive sheet, it is appropriate that the peel strength to the glass plate measured after the adhesive sheet is stored at 60°C for 7 days and is attached to a glass plate as an adherend and subjected to a heat treatment at 180°C for 1 hour (peel strength to the glass plate after storage / heating) FS1 is less than 3N / 20mm, and preferably less than 1.0N / 20mm. An adhesive sheet showing the above-mentioned peel strength to the glass plate after storage / heating FS1 has heat-resistant easy peelability after heat treatment even when stored for a long time or when the temperature conditions during storage change, and has good storage stability. From the viewpoint of peelability, the above-mentioned peel strength to the glass plate after storage / heating FS1 is preferably less than 0.8N / 20mm, more preferably less than 0.6N / 20mm, further preferably less than 0.5N / 20mm, particularly preferably less than 0.4N / 20mm, and may also be less than 0.3N / 20mm. The lower limit of the peel strength FS1 of the glass plate after storage / heating may be 0.0 N / 20 mm, or may be 0.01 N / 20 mm or more (e.g., 0.1 N / 20 mm or more). Specifically, the peel strength FS1 of the glass plate after storage / heating refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min after the adhesive sheet is attached to the adherend after being stored at 60° C. for 7 days and subjected to a heating treatment at 180° C. for 1 hour at 23° C.

[0051] The above-mentioned glass plate peel strength FS1 after storage / heating is more specifically measured by the following method.

[0052] Store the adhesive sheet at 60°C for 7 days. Use the adhesive sheet after storage to prepare an evaluation sample by the method described in the determination of the initial peel strength F0. Heat the obtained evaluation sample in an oven at 180°C for 1 hour and let it stand for 30 minutes at 23°C and 50% RH. Then, place the evaluation sample in a tensile testing machine under the same environment, and measure the peel strength (peel strength on the glass plate after storage / heating) FS1 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min. The adherend, tensile testing machine, and other matters are the same as the determination of the initial peel strength F0.

[0053] (FS1 / FS0)

[0054] In some embodiments, the storage / post-heating peel strength FS1 [N / 20mm] of the adhesive sheet is lower than 100% of the post-storage peel strength FS0. In other words, the ratio (FS1 / FS0) of the adhesive sheet is lower than 1. It is appropriate that the above (FS1 / FS0) is less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and may also be less than 0.15. The adhesive sheet satisfying this characteristic can be well bonded to the adherend even after storage, and can exhibit good heat peelability and heat-resistant peelability when peeled off after heat treatment, so it has excellent storage stability. The lower limit of the above ratio (FS1 / FS0) is not particularly limited, for example, it can be about 0.01 or more.

[0055] (Total amount of released gas when kept at 180℃ for 1 hour)

[0056] The total amount of released gas of the adhesive sheet disclosed herein when kept at 180°C for 1 hour is preferably 1000μg or less (also referred to as 1000μg / g or less) per 1g of the adhesive sheet. In the adhesive sheet satisfying this characteristic, the released gas from the adhesive sheet is limited to a prescribed amount or less, so it is not easy to cause adverse conditions caused by the released gas (such as adherend contamination, reduction in vacuum, etc.). From this point of view, in some preferred embodiments, the total amount of released gas of the adhesive sheet when kept at 180°C for 1 hour is 950μg / g or less, more preferably 900μg / g or less, further preferably 850μg / g or less, particularly preferably 800μg / g or less, and can be 750μg / g or less, or 700μg / g or less. The lower the lower limit of the total amount of released gas of the adhesive sheet when kept at 180°C for 1 hour, the more preferred it is, and it can be about 1μg / g or more (for example, 10μg / g or more or 100μg / g or more). The total amount of released gas when the pressure-sensitive adhesive sheet is kept at 180° C. for 1 hour is specifically measured by the method described in Examples below.

[0057] <Adhesive layer>

[0058] (polymer)

[0059] In the technology disclosed herein, the type of adhesive is not particularly limited. The adhesive layer (layer formed by the adhesive) may include one or more polymers of various rubber-like polymers such as acrylic polymers, rubber polymers (such as natural rubber, synthetic rubber, mixtures thereof, etc.), polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, fluorine polymers, etc. that can be used in the field of adhesives. The above polymers are used as base polymers in the adhesive and can function as structural polymers of the molding adhesive. From the viewpoints of adhesive performance, cost, etc., it is preferred to use an adhesive containing an acrylic polymer or a rubber polymer as a base polymer. Among them, an adhesive (acrylic adhesive) using an acrylic polymer with excellent heat resistance as a base polymer is preferred.

[0060] Hereinafter, the acrylic pressure-sensitive adhesive and the pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive, that is, the pressure-sensitive adhesive sheet having the acrylic pressure-sensitive adhesive layer will be mainly described, but the pressure-sensitive adhesive layer disclosed herein is not intended to be limited to the acrylic pressure-sensitive adhesive layer.

[0061] (Acrylic polymer)

[0062] In some embodiments, as an acrylic polymer, an acrylic polymer in which more than 50% by weight of the monomer components constituting the polymer are acrylic monomers is used. It is appropriate that the proportion of acrylic monomers in the above-mentioned monomer components is 60% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, for example, it can be 90% by weight or more. The upper limit of the proportion of acrylic monomers in the monomer components constituting the acrylic polymer is 100% by weight. From the viewpoint of obtaining the effect of using non-acrylic monomers, the proportion of the above-mentioned acrylic monomers can be, for example, 98% by weight or less, 95% by weight or less, or 92% by weight or less. Acrylic monomers can be used alone or in combination of two or more.

[0063] In some embodiments, the monomer component includes an alkoxy-containing (meth)acrylate. According to the acrylic polymer containing an alkoxy-containing (meth)acrylate as a monomer component, for example, there is a tendency to easily obtain compatibility with the multifunctional monomer described later. The alkoxy-containing (meth)acrylate can be used alone or in combination of two or more.

[0064] Examples of (meth)acrylates containing an alkoxy group include alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; alkoxy (poly)alkylene glycol (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate; and the like. Among them, alkoxyalkyl (meth)acrylates are preferred, and among them, alkoxyalkyl (meth)acrylates having an alkoxy group having 1 to 4 carbon atoms (eg, 1, 2, or 3 carbon atoms) are more preferred, and methoxyethyl (meth)acrylate is particularly preferred.

[0065] The content of the alkoxy-containing (meth)acrylate in the monomer component constituting the acrylic polymer is not particularly limited. From the viewpoint of effectively obtaining the effect brought about by the use of the alkoxy-containing (meth)acrylate, the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is usually about 1% by weight or more, for example, it can be 10% by weight or more, it can be 30% by weight or more, and it can also be 50% by weight or more. In some embodiments, from the viewpoint of adhesive properties such as adhesive strength and compatibility with multifunctional monomers, the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more. The upper limit of the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is 100 weight % or less. For example, from the viewpoint of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the content of the alkoxy-containing (meth)acrylate is advantageously about 99 weight % or less, and can be 95 weight % or less, 93 weight % or less, or 90 weight % or less.

[0066] In some other embodiments, the monomer component constituting the acrylic polymer may be a component containing a linear alkyl (meth)acrylate having a linear or branched alkyl group with 1 to 20 carbon atoms at the ester terminal. Hereinafter, a linear alkyl (meth)acrylate having an alkyl group with X to Y carbon atoms at the ester terminal may be referred to as “C X-YAlkyl (meth) acrylate". It should be noted that in the present specification, the term "chain" is used to include linear and branched chains. The above-mentioned chain alkyl (meth) acrylates can be used alone or in combination of two or more.

[0067] As C 1-20 Specific non-limiting examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.

[0068] Among these, it is preferred to use at least C 4-20 Alkyl (meth) acrylate, more preferably at least C 4-18 In some embodiments, as C 1-20 Alkyl (meth) acrylate, preferably C 4-8 Among them, it is more preferred to use C 4-8 Alkyl acrylate. 4-8 The alkyl (meth)acrylate can be used alone or in combination of two or more. 4-8 The use of alkyl (meth) acrylates tends to easily obtain good adhesive properties (adhesive strength, etc.). For example, as the above-mentioned monomer component, an acrylic polymer containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) is preferred, and an acrylic polymer containing at least 2EHA is particularly preferred. 1-20 In some other forms of alkyl (meth) acrylate, C 7-12 Alkyl (meth) acrylate. 7-12 The alkyl (meth)acrylate can be used alone or in combination of two or more. 7-12 Alkyl (meth) acrylate, preferably C7-10 Alkyl acrylate, more preferably C 7-9 The alkyl acrylate is more preferably a C8 alkyl acrylate.

[0069] Among the monomer components constituting the acrylic polymer, 1-20 The content of alkyl (meth) acrylate is not particularly limited. 1-20 From the viewpoint of the effect of using alkyl (meth)acrylate, C 1-20 The content of the alkyl (meth) acrylate is generally about 1% by weight or more, for example, 10% by weight or more, 30% by weight or more, or 50% by weight or more. In some embodiments, from the perspective of adhesive properties such as adhesive strength, the C 1-20 The content of the alkyl (meth)acrylate is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. 1-20 The upper limit of the content of the alkyl (meth) acrylate is 100 wt % or less. For example, from the perspective of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the C 1-20 The content of alkyl (meth) acrylate is advantageously about 99 wt % or less, and may be 95 wt % or less, 93 wt % or less, or 90 wt % or less. 1-20 The content of alkyl (meth) acrylate can range from 1-20 The above C included in the alkyl (meth) acrylate 4-20 Alkyl (meth) acrylate, C 4-18 Alkyl (meth) acrylate, C 4-8 Alkyl (meth) acrylate, C 4-8 Alkyl acrylate, C 7-12 Alkyl (meth) acrylate, C 7-10 Alkyl acrylate, C 7-9 The range of each content of alkyl acrylate, C8 alkyl acrylate, BA, and 2EHA.

[0070] In some embodiments, the monomer components constituting the acrylic polymer preferably include other monomers other than the above-mentioned alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. Such other monomers may be monomers (copolymerizable monomers) that can be copolymerized with alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. As the above-mentioned other monomers, monomers having polar groups (e.g., carboxyl groups, hydroxyl groups, rings containing nitrogen atoms, etc.) may be preferably used. Monomers having polar groups may help introduce crosslinking points into acrylic polymers and improve the cohesive force of adhesives. Other monomers may be used alone or in combination of two or more.

[0071] Specific non-limiting examples of other monomers include the following monomers.

[0072] Carboxyl group-containing monomers: for example, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like.

[0073] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.

[0074] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0075] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, (meth)acrylate sulfopropyl ester, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0076] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl (meth)acrylate ether, allyl glycidyl ether, and glycidyl (meth)acrylate ether.

[0077] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.

[0078] Isocyanate group-containing monomer: for example, 2-isocyanateethyl (meth)acrylate, etc.

[0079] Amide-containing monomers: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di (n-Butyl) N,N-dialkyl(meth)acrylamide, such as N-(meth)acrylamide, N,N-di(tert-butyl)(meth)acrylamide; N-monoalkyl(meth)acrylamide, such as N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; N-vinylcarboxylic acid amides, such as N-vinylacetamide; monomers having hydroxyl groups and amide groups, such as N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide N-hydroxyalkyl (meth) acrylamide, N-(2-hydroxybutyl) (meth) acrylamide, N-(3-hydroxybutyl) (meth) acrylamide, N-(4-hydroxybutyl) (meth) acrylamide and the like; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl (meth) acrylamides such as N-methoxymethyl (meth) acrylamide, N-methoxyethyl (meth) acrylamide, N-butoxymethyl (meth) acrylamide; and N,N-dimethylaminopropyl (meth) acrylamide, N-(meth)acryloyl morpholine, alkoxy diacetone (meth) acrylamide, vinyl formamide, vinyl acetamide, and the like.

[0080] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0081] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0082] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam).

[0083] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.

[0084] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.

[0085] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.

[0086] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0087] Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane.

[0088] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.

[0089] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0090] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0091] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.

[0092] (Meth)acrylates having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, and the like.

[0093] (Meth)acrylates having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like.

[0094] In addition, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates containing halogen atoms such as (meth)acrylates containing vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as silicone (meth)acrylates, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0095] When using such other monomers, its usage amount is not particularly limited, and it is appropriate to be set as more than 0.01 weight % of the overall monomer component. From the viewpoint of better exerting the use effect of other monomers, the usage amount of other monomers can be set as more than 0.1 weight % of the overall monomer component, and can be set as more than 0.5 weight %. In addition, from the viewpoint of easily obtaining the balanced property of adhesive properties, it is appropriate to set the usage amount of other monomers as less than 50 weight % of the overall monomer component, and preferably be set as less than 40 weight %.

[0096] In some embodiments, the monomer components constituting the acrylic polymer may include a monomer having a nitrogen atom. By using a monomer having a nitrogen atom, the cohesive force of the adhesive is increased, and the adhesive force can preferably be increased. The monomer having a nitrogen atom can be used alone or in combination of two or more. As a suitable example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a nitrogen atom and a monomer having a ring containing a nitrogen atom, the monomers exemplified above can be used, for example, N-vinyl cyclic amide represented by the general formula (1) can be used:

[0097] [Chemical formula 1]

[0098]

[0099] Here, in the general formula (1), R 1 is a divalent organic group, specifically -(CH2) n-. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone (NVP) can be preferably used. Other suitable examples of monomers having nitrogen atoms include: N,N-dialkyl (meth)acrylamides such as (meth)acrylamide and N,N-dimethyl (meth)acrylamide; N-monoalkyl (meth)acrylamides such as N-isopropyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamides such as N-(2-hydroxyethyl)acrylamide (HEAA); N-acryloylmorpholine (ACMO); alkoxy diacetone (meth)acrylamide; vinyl formamide, vinyl acetamide; and the like. Among them, NVP, HEAA, and ACMO are more preferred.

[0100] The usage amount of the monomer with nitrogen atom (preferably the monomer with ring containing nitrogen atom) is not particularly limited, for example, it can be more than 1% by weight of the whole monomer component, or it can be more than 3% by weight. In some ways, the usage amount of the monomer with nitrogen atom in the above-mentioned monomer component is preferably more than 5% by weight, more preferably more than 7% by weight, and further preferably more than 9% by weight. In addition, it is appropriate to set the usage amount of the monomer with nitrogen atom to less than 40% by weight of the whole monomer component, which can be set to less than 35% by weight, can be set to less than 30% by weight, or can be set to less than 25% by weight. In some ways, the usage amount of the monomer with nitrogen atom can be set to less than 20% by weight of the whole monomer component, which can be set to less than 15% by weight, or can be set to less than 12% by weight.

[0101] In some embodiments, the monomer component may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesion and crosslinking density of the adhesive can be adjusted, and the bonding strength can be improved. As a monomer containing a hydroxyl group, the monomers exemplified above can be used, for example, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) can be preferably used. The monomer containing a hydroxyl group can be used alone or in combination of two or more.

[0102] The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the entire monomer component, it can be more than 0.1% by weight, and it can also be more than 0.5% by weight. In some preferred embodiments, the amount of the monomer containing a hydroxyl group is more than 1% by weight of the entire monomer component, more preferably more than 2% by weight, and further preferably more than 3% by weight, for example, it can be more than 5% by weight. In addition, in some embodiments, it is appropriate to set the amount of the monomer containing a hydroxyl group to, for example, less than 40% by weight of the entire monomer component, preferably less than 30% by weight, more preferably less than 20% by weight, more preferably less than 10% by weight, and it can also be less than 7% by weight.

[0103] In some preferred embodiments, as monomer components of acrylic polymers, as monomers having polar groups (monomers containing polar groups), monomers having nitrogen atoms (e.g., monomers containing amide groups such as (meth)acrylamide, monomers containing rings containing nitrogen atoms such as NVP) and monomers containing hydroxyl groups (e.g., HEA, 4HBA) are used together. In this way, it is possible to achieve both adhesive force and cohesive force in a well-balanced manner. In the embodiment in which a monomer having nitrogen atoms and a monomer containing hydroxyl groups are used together, the amount of the monomer having nitrogen atoms is A N The amount of monomer containing hydroxyl group A OH Weight ratio (A N / A OH ) is not particularly limited, and can be, for example, 0.1 or more, 0.5 or more, 1.0 or more, 1.2 or more, 1.5 or more, or 1.8 or more. N / A OH ) For example, it can be less than 10, less than 5, less than 3, or less than 2.5.

[0104] In some embodiments, the monomer component includes a monomer containing a carboxyl group. Suitable examples of monomers containing a carboxyl group include acrylic acid (AA) and methacrylic acid (MAA). Monomers containing a carboxyl group can be used alone or in combination of two or more. For example, AA and MAA can also be used in combination.

[0105] The usage amount of the monomer containing carboxyl can be, for example, more than 0.01 % by weight of the overall monomer component, can be more than 0.05 % by weight, can be more than 0.1 % by weight, can be more than 0.3 % by weight, and can also be more than 0.5 % by weight. The ratio of the above-mentioned monomer containing carboxyl can be, for example, less than 15 % by weight, can be less than 10 % by weight, can be less than 5 % by weight, can be less than 3 % by weight, can be less than 2 % by weight, and can also be less than 1 % by weight (for example, less than 1 % by weight).

[0106] In the acrylic polymer, as other monomer components, a multifunctional monomer having a polymerizable functional group (typically a free radical polymerizable functional group) having at least 2 (meth)acryloyl groups, vinyl groups, etc. with unsaturated double bonds can be included. As a monomer component, by using a multifunctional monomer, the cohesive force of the adhesive can be improved. The multifunctional monomer can be used as a crosslinking agent. As the multifunctional monomer, there is no particular limitation, for example, a suitable substance among the substances exemplified as the multifunctional monomer contained in the adhesive layer described later can be used alone or in combination of two or more.

[0107] The usage amount of the multifunctional monomer is not particularly limited, and can be appropriately set in a manner that achieves the purpose of use of the multifunctional monomer. The usage amount of the multifunctional monomer can be set to less than about 3 wt % of the above-mentioned monomer component, preferably less than about 2 wt %, more preferably less than about 1 wt % (e.g., less than about 0.5 wt %). The lower limit of the usage amount when using a multifunctional monomer is greater than 0 wt %, and is not particularly limited. Usually, by setting the usage amount of the multifunctional monomer to more than about 0.001 wt % of the monomer component (e.g., more than about 0.01 wt %), the use effect of the multifunctional monomer can be appropriately exerted.

[0108] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to about 20°C to 170°C (typically about 40°C to 140°C).

[0109] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; etc., or a mixed solvent of two or more can be used.

[0110] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. For example, without particular limitation, an azo polymerization initiator, a peroxide polymerization initiator, a redox polymerization initiator based on a combination of a peroxide and a reducing agent, a substituted ethane polymerization initiator, etc. can be used. As the polymerization initiator, for example, one or more of the substances exemplified as thermal polymerization initiators that can be added to the adhesive layer described later can be selected and used.

[0111] The amount of the polymerization initiator used can be set to a normal amount corresponding to the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example, about 0.01 to 1 part by weight) of the polymerization initiator can be used relative to 100 parts by weight of all monomer components of the polymerization object.

[0112] The molecular weight of the polymer (for example, an acrylic polymer) is not particularly limited and can be set within an appropriate range depending on the required performance, etc. The weight average molecular weight (Mw) of the above polymer is about 1×10 4 The above is suitable, for example, it can be about 10×10 4 By using a polymer having an Mw of a predetermined value or more, cohesive force and adhesive force can be achieved in a well-balanced manner. In some embodiments, the Mw may be 20×10 4 Above, it can be 30×10 4 Above, it can be about 40×10 4 Above, it can be about 50×10 4 For example, it can be about 55×10 4 The upper limit of the Mw of the above polymer is not particularly limited, and can be, for example, about 1000×10 4 Below, it can also be about 100×10 4 Here, Mw refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (chromatographic column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used.

[0113] It should be noted that, in the technology disclosed herein, as polymer, polymers (the amount of ethylenically unsaturated groups is less than 0.01mmol / g) that do not substantially have ethylenically unsaturated groups such as acryloyl, methacryloyl, vinyl, allyl can be used. In some other ways, in the scope of the effect brought by the technology disclosed herein without damaging, the adhesive layer can include polymers with ethylenically unsaturated groups. As polymers with ethylenically unsaturated groups, for example, polymers with ethylenically unsaturated groups in side chains can be used. It is appropriate that the content of the polymer with ethylenically unsaturated groups in the adhesive layer is less than 10 weight %, preferably less than 3 weight %, more preferably less than 1 weight %. The technology disclosed herein can preferably be implemented using an adhesive that does not substantially contain polymers with ethylenically unsaturated groups.

[0114] (Multifunctional monomer)

[0115] In the adhesive layer, in addition to the above-mentioned polymer, a multifunctional monomer is also contained. By making the multifunctional monomer be included in the adhesive layer in a state before reaction (unreacted), the multifunctional monomer reacts when heated at high temperature, so that the adhesive force is reduced or the rise of the peeling force is suppressed, and heating easy peeling can be achieved. By including a multifunctional monomer, a thermosetting adhesive having heat-resistant easy peeling after heat treatment can be obtained. More specifically, usually, when heated at high temperature in a state of being attached to an adherend, the adhesive will be adsorbed on the surface of the adherend. Therefore, the adhesive force of the adhesive to the adherend is enhanced, and heavy peeling will occur. According to the technology disclosed herein, by making the adhesive contain a multifunctional monomer of more than a specified amount, the reaction of the multifunctional monomer is rapidly carried out when heated, and the adhesive curing can be carried out in advance compared with the adsorption of the adhesive to the adherend. Thus, the adhesive force to the adherend can be reduced. Further, even if the heating continues afterwards, the adhesive force of the adhesive to the adherend will not rise, but is maintained within a specified range, so the adhesive will play an excellent heating easy peeling property. It should be noted that the technology disclosed herein is not limited to the above explanation. The polyfunctional monomer can be used alone or in combination of two or more.

[0116] It should be noted that in this specification, the so-called multifunctional monomer refers to a polymerizable compound having more than two ethylenically unsaturated groups in one molecule, and also includes substances called oligomers. The above-mentioned ethylenically unsaturated groups function as polymerizable functional groups (typically free radical polymerizable functional groups). Examples of ethylenically unsaturated groups possessed by multifunctional monomers include acryloyl, methacryloyl, vinyl and allyl groups, but are not limited to these. Suitable examples of ethylenically unsaturated groups include acryloyl and methacryloyl. Among them, acryloyl is preferred. Hereinafter, compounds having more than two acryloyl and / or methacryloyl groups are sometimes referred to as multifunctional acrylic monomers. In addition, compounds having more than two vinyl groups are sometimes referred to as multifunctional vinyl monomers.

[0117] In addition, in the technology disclosed herein, a multifunctional monomer having a weight loss rate of 1% or less (specifically, 1.0% or less) when reaching 180°C in TGA under a heating condition of 10°C / min is used. By using a heat-resistant multifunctional monomer having the above-mentioned 180°C heating weight loss rate of 1% or less (hereinafter, also referred to as a "heat-resistant multifunctional monomer"), the adhesive layer has heat-resistant peelability based on the use of the multifunctional monomer, and the generation of released gas during heating is suppressed. By using the above-mentioned heat-resistant multifunctional monomer, it is possible to achieve both heat-resistant peelability and reduced released gas. From the viewpoint of reduced released gas, in some preferred embodiments, the 180°C heating weight loss rate of the heat-resistant multifunctional monomer is 0.9% or less, more preferably 0.8% or less, further preferably 0.7% or less, particularly preferably 0.6% or less, and may also be 0.5% or less. The lower limit of the 180°C heating weight loss rate of the heat-resistant multifunctional monomer is theoretically 0%, and can be 0.1% or more, 0.2% or more, or 0.3% or more in practice. The heat-resistant multifunctional monomer can be used alone or in combination of two or more. The 180°C heating weight loss rate of the multifunctional monomer is specifically measured by the method described in the examples described later.

[0118] The number of ethylenically unsaturated groups contained in one molecule of a heat-resistant multifunctional monomer is preferably 3 or more, more preferably 4 or more, further preferably 5 or more, and may be 6 or more. The more ethylenically unsaturated groups there are in a heat-resistant multifunctional monomer, the better the curability during heating, and the easier it is to obtain a tendency to be easily peelable by heating. In addition, by using a heat-resistant multifunctional monomer with more ethylenically unsaturated groups (functional groups), it is possible to obtain easily peelable by heating with a relatively small amount of use. This reduces the amount of released gas from the heat-resistant multifunctional monomer, which is advantageous. The upper limit of the number of ethylenically unsaturated groups in one molecule of a heat-resistant multifunctional monomer is not limited to a specific range, for example, it may be less than 50, may be less than 40, may be less than 30, may be less than 20, or may be less than 15. In some embodiments, the number of ethylenically unsaturated groups in one molecule of a heat-resistant multifunctional monomer may be, for example, less than 10, may be less than 8, or may be less than 6. The heat-resistant multifunctional monomer having the above number of ethylenically unsaturated groups tends to easily achieve both good adhesiveness and heat-peelability, and also to be excellent in storage stability.

[0119] As the heat-resistant multifunctional monomer, various multifunctional acrylate monomers and multifunctional vinyl monomers having 2 or more ethylenically unsaturated groups can be used. Among them, multifunctional acrylate monomers can be preferably used. Although not particularly limited, multifunctional acrylate monomers tend to exhibit desired properties with good compatibility by being used in combination with acrylic polymers. Multifunctional acrylate monomers and multifunctional vinyl monomers can be used alone or in combination of two or more.

[0120] As the multifunctional monomer, one or more compounds having a weight loss rate of 1% or less upon heating at 180° C. can be selected and used from the following multifunctional monomers: 1,12-dodecanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, alkylene oxide-modified bisphenol A di(meth)acrylate, alkylene oxide-modified neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate. , vinyl (meth)acrylate, divinylbenzene and other bifunctional monomers; trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, glycerol propoxy triacrylate, tetramethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate and other trifunctional monomers; pentaerythritol alkoxy tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate and other quadrifunctional monomers; sorbitol penta(meth)acrylate, dipentaerythritol penta(meth)acrylate and other pentafunctional monomers; dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, alkylene oxide-modified hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate and other hexafunctional monomers; and epoxy acrylates, polyester acrylates, urethane acrylates and the like having two or more functionalities. Among them, trimethylolpropane tri(meth)acrylate and dipentaerythritol hexa(meth)acrylate are mentioned as preferred examples. Among them, dipentaerythritol hexa(meth)acrylate is particularly preferred.

[0121] Although not particularly limited, it is appropriate to use a monomer with a molecular weight of 100 or more as a heat-resistant multifunctional monomer. In some preferred embodiments, the molecular weight of the heat-resistant multifunctional monomer is, for example, 250 or more, more preferably 300 or more, 350 or more, 400 or more, 450 or more, or 500 or more. As the above-mentioned heat-resistant multifunctional monomer, a compound with a molecular weight of 300 or more is preferably used. In addition, the molecular weight of the heat-resistant multifunctional monomer is generally about 100,000 or less, for example, about 10,000 or less (for example, less than 10,000) is appropriate, preferably 5,000 or less (for example, less than 5,000), 1,500 or less, 1,000 or less (for example, less than 1,000), 800 or less, or 600 or less. The use of a heat-resistant multifunctional monomer with a molecular weight in the above range is advantageous, for example, in terms of the preparation and coating properties of the adhesive composition. It should be noted that the above molecular weight is a molecular weight calculated according to the manufacturer's nominal value or molecular structure. For the heat-resistant multifunctional monomer having a molecular weight equal to or greater than a predetermined value, the value of the weight average molecular weight (Mw) in terms of standard polystyrene obtained by GPC may be adopted.

[0122] In some embodiments, the content of the heat-resistant multifunctional monomer in the adhesive layer is preferably 30 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. Suitable acrylic polymer) contained in the adhesive layer. By including a sufficient amount of heat-resistant multifunctional monomer in the adhesive layer, the multifunctional monomer reacts rapidly when heated, and the adhesive is thermally cured, thereby achieving easy peeling by heating. The appropriate amount of the heat-resistant multifunctional monomer may vary according to its molecular weight, the number of functional groups, etc. In some preferred embodiments, from the perspective of easy peeling by heating, it is appropriate to set the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer to be 50 parts by weight or more, preferably 60 parts by weight or more, more preferably 70 parts by weight or more, further preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and may also be 100 parts by weight or more. The upper limit of the content of the heat-resistant multifunctional monomer in the adhesive layer is not particularly limited, and can be set in a manner to achieve the desired adhesive properties. In some embodiments, from the perspective of compatibility with a polymer (specifically, a base polymer, such as an acrylic polymer), the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer is appropriately set to about 200 parts by weight or less, preferably 160 parts by weight or less, more preferably 150 parts by weight or less, further preferably 140 parts by weight or less, and can be 120 parts by weight or less, or can be 90 parts by weight or less.

[0123] The adhesive layer disclosed herein contains the above-mentioned polymer (specifically, a base polymer. For example, an acrylic polymer) and a heat-resistant multifunctional monomer (for example, a multifunctional acrylic monomer). In some embodiments, from the perspective of effectively exerting the effects brought about by the technology disclosed herein, it is appropriate that the total proportion of the above-mentioned polymer and the heat-resistant multifunctional monomer in the entire adhesive layer is 50% by weight or more (for example, more than 50% by weight and less than 100% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and may also be 95% by weight or more.

[0124] (Other multifunctional monomers)

[0125] In addition, the adhesive layer may contain a polyfunctional monomer (other polyfunctional monomer) whose weight reduction rate exceeds 1% when reaching 180°C in TGA under the temperature rising condition of 10°C / min, within the range not impairing the effect brought by the technology disclosed herein. As other polyfunctional monomers, known polyfunctional acrylate monomers and vinyl monomers can be used. In some embodiments, it is appropriate to set the content of other polyfunctional monomers in the adhesive layer to about 100 parts by weight or less (0 parts by weight or more and 100 parts by weight or less. For example, less than 100 parts by weight) relative to 100 parts by weight of the above-mentioned heat-resistant polyfunctional monomer, and it may be less than 50 parts by weight, less than 30 parts by weight, less than 10 parts by weight, or less than 1 part by weight. The technology disclosed herein is preferably implemented in a manner in which the adhesive layer does not substantially contain other polyfunctional monomers.

[0126] (Monofunctional monomer)

[0127] In addition, in the adhesive layer, according to the expectation, one or more monofunctional monomers containing one ethylenically unsaturated group in one molecule may also be included. The monofunctional monomer can be used within the scope of the effect brought by the technology disclosed herein. As the monofunctional monomer, known monofunctional acrylate monomers and vinyl monomers can be used. Although not particularly limited, the content of the monofunctional monomer in the adhesive layer is set to about 100 weight parts or less (0 weight parts or more and 100 weight parts or less) relative to 100 weight parts of the multifunctional monomer. For example, less than 100 weight parts) is appropriate, and can be less than 50 weight parts, can be less than 30 weight parts, can be less than 10 weight parts, can also be less than 1 weight part. The technology disclosed herein can be implemented in a manner that the adhesive layer is substantially free of monofunctional monomers.

[0128] (Thermal polymerization initiator)

[0129] In some embodiments, it is preferred that the adhesive layer further contains a thermal polymerization initiator in addition to the above-mentioned polymer and multifunctional monomer. Here, the so-called thermal polymerization initiator refers to a polymerization initiator that generates free radicals by heating. By including a thermal polymerization initiator in the adhesive layer, the thermal polymerization initiator reacts with the multifunctional monomer when heated at a high temperature to reduce the adhesive force or suppress the increase in the adhesive force, and it is possible to achieve heat-resistant peelability. By including a thermal polymerization initiator, a thermosetting adhesive having heat-resistant peelability even after heat treatment can be ideally obtained.

[0130] The thermal polymerization initiator is not particularly limited, and for example, a peroxide polymerization initiator, an azo polymerization initiator, a redox polymerization initiator based on a combination of a peroxide and a reducing agent, a substituted ethane polymerization initiator, and the like can be used. Specifically, examples include: persulfates such as potassium persulfate and ammonium persulfate; peroxide compounds such as benzoyl peroxide (BPO), tert-butyl hydroperoxide, and hydrogen peroxide; azo compounds such as 2,2'-azobisisobutyronitrile (AIBN) and 2,2'-azobis(N-butyl-2-methylpropionamide); substituted ethane initiators such as phenyl-substituted ethane; redox initiators based on a combination of peroxides and reducing agents such as a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate, and the like. These thermal polymerization initiators can be used alone or in combination of two or more. Although not particularly limited, in the technology disclosed herein, as the thermal polymerization initiator contained in the adhesive layer, it is preferably implemented in a manner using a peroxide polymerization initiator, an azo polymerization initiator, or a combination of both.

[0131] In some embodiments, as a thermal polymerization initiator, a thermal polymerization initiator with a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. Here, the so-called 10-hour half-life temperature of the polymerization initiator refers to the temperature at which the concentration of the initiator becomes half after 10 hours, and is used as an index to indicate the decomposition rate of the polymerization initiator and the thermal decomposition property (free radical generation property) at a specified temperature. In this specification, as the 10-hour half-life temperature of the thermal polymerization initiator, the nominal value recorded in the manufacturer's catalog, etc. is adopted. For the case where there is no manufacturer's nominal value, the value measured using an appropriate solvent (such as toluene) can be adopted. Although it is believed that the thermal decomposition property of the thermal polymerization initiator in the adhesive is different from the thermal decomposition property in the solvent, the thermal polymerization initiator with a high 10-hour half-life temperature has a tendency to have excellent heat resistance and excellent storage stability. From such a point of view, the 10-hour half-life temperature of the thermal polymerization initiator can be above 55°C, above 60°C, above 65°C, or above 70°C. In some other embodiments, the 10-hour half-life temperature of the thermal polymerization initiator may be above 80°C, above 90°C, or above 100°C (e.g., above 100°C). In addition, the upper limit of the 10-hour half-life temperature of the thermal polymerization initiator is, for example, below 150°C, and it is appropriate to be below 120°C. In some embodiments, the 10-hour half-life temperature of the thermal polymerization initiator is appropriately about 100°C or below (e.g., below 100°C), and may be below 95°C, below 90°C, below 85°C, or below 80°C.

[0132] In some embodiments, as a thermal polymerization initiator, it is preferred to use at least an azo polymerization initiator. When an azo polymerization initiator is used as a thermal polymerization initiator, there is a tendency for the amount of released gas from the adhesive to decrease. In addition, according to the adhesive containing an azo polymerization initiator as a thermal polymerization initiator, even in the case of long-term storage, when there is a temperature change during storage, etc., the desired heat-peelable property can be maintained after storage. By using an azo polymerization initiator as a thermal polymerization initiator, an adhesive with good storage stability can be formed. As a reason for this, it is believed that this is because compared with other types of polymerization initiators, the azo polymerization initiator has good thermal stability in an adhesive containing a polymer and a multifunctional monomer, but the technology disclosed herein is not limited to the above-mentioned investigation. Azo polymerization initiators can be used alone or in combination of two or more.

[0133] The azo polymerization initiator used in the art disclosed herein is not particularly limited, and any of azonitrile compounds, azoamide compounds, azoester compounds, alkylazo compounds, azoamidine compounds, azoimidazoline compounds, and polymeric azo compounds can be used. Specific examples of the azo polymerization initiator include AIBN, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 4,4-azobis(4-cyanovaleric acid), 2,2'-azobis(N-butyl-2-methylpropionamide), dimethyl 2,2'-azobis(2-methylpropionate), 1,1'-azobis(1-cyclohexanecarboxylic acid) dimethyl ester, 2,2'-azobis(2-methylpropane), 2,2'-azobis(2 ,4,4-trimethylpentane), 2-tert-butylazo-2-cyanopropane, 4,4'-azobis(3,3,4,4,5,5,6,6,7,7,8,8,8-tri-N,N'-dimethyleneisobutylamidine), 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, azocumene, etc.

[0134] Although not particularly limited, as the above-mentioned azo polymerization initiator, an azo polymerization initiator having a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. The above-mentioned thermal polymerization initiator with a high 10-hour half-life temperature tends to have excellent heat resistance and excellent storage stability. From the above viewpoint, the 10-hour half-life temperature of the above-mentioned azo polymerization initiator is preferably 55°C or more, more preferably 60°C or more, further preferably 65°C or more, particularly preferably 70°C or more, can be 80°C or more, can be 90°C or more, and can also be 100°C or more (for example, more than 100°C). The upper limit of the 10-hour half-life temperature of the azo polymerization initiator is, for example, 150°C or less, and 120°C or less is appropriate. In some preferred embodiments, an azo polymerization initiator having a 10-hour half-life temperature of, for example, 100°C or less (for example, less than 100°C, 95°C or less, or 90°C or less) can be used.

[0135] The content of the azo polymerization initiator in the adhesive layer is not particularly limited, and can be set to 0.1 weight part or more (0.10 weight part or more) relative to 100 weight parts of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive layer. For example, by including a prescribed amount or more of an azo polymerization initiator in the adhesive layer, the azo polymerization initiator is fully in contact with the multifunctional monomer, and the reaction of the two can be carried out rapidly. Thus, it is ideal to achieve easy peeling by heating. In addition, by making the adhesive layer include an azo polymerization initiator, it is possible to have good storage stability. From the above viewpoint, the amount of the azo polymerization initiator relative to 100 weight parts of the above-mentioned polymer is preferably 0.15 weight part or more, more preferably 0.20 weight part or more, further preferably 0.25 weight part or more, can be 0.30 weight part or more, can be 0.35 weight part or more, can be 0.40 weight part or more, can be 0.45 weight part or more, and can also be 0.50 weight part or more. The upper limit of the content of the azo polymerization initiator in the adhesive layer is not particularly limited, and can be appropriately set in a manner that does not damage the adhesive properties such as adhesive force and storage stability. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) is, for example, less than 3 parts by weight, which is appropriate, preferably less than 2.5 parts by weight, more preferably less than 2.0 parts by weight, further preferably less than 1.5 parts by weight, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.8 parts by weight, and can also be less than 0.6 parts by weight (for example, less than 0.4 parts by weight). In addition, by limiting the amount of the azo polymerization initiator used, the generation of released gas from the azo polymerization initiator can be suppressed.

[0136] The content of the azo polymerization initiator in the adhesive layer can also be determined by the relative relationship with the multifunctional monomer. In some embodiments, from the viewpoint of the contact probability with the multifunctional monomer, it is appropriate to set the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 0.1 parts by weight or more (0.10 parts by weight or more), preferably 0.15 parts by weight or more, more preferably 0.20 parts by weight or more, further preferably 0.25 parts by weight or more, can be 0.30 parts by weight or more, can be 0.35 parts by weight or more, can be 0.40 parts by weight or more, can be 0.45 parts by weight or more, and can also be 0.50 parts by weight or more. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer is, for example, appropriately about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), may be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), may be less than 0.8 parts by weight, or may be less than 0.6 parts by weight (for example, less than 0.4 parts by weight).

[0137] In some embodiments, the adhesive layer may contain only an azo polymerization initiator as a thermal polymerization initiator, or contain an azo polymerization initiator and a thermal polymerization initiator different from the azo polymerization initiator (non-azo polymerization initiator). In the embodiment in which only an azo polymerization initiator is used, the effect of the use of the azo polymerization initiator can be maximized, and in the embodiment in which an azo polymerization initiator and a non-azo polymerization initiator are used together, the effects and characteristics based on the azo polymerization initiator and the non-azo polymerization initiator can be utilized. In some embodiments, it is appropriate that the proportion of the azo polymerization initiator to the total thermal polymerization initiator contained in the adhesive layer is set to about 10% by weight or more. From the perspective of effectively exerting the effect of the azo polymerization initiator, it is preferably 30% by weight or more, more preferably 40% by weight or more, and further preferably 50% by weight or more (for example, more than 50% by weight), and can be 55% by weight or more, or 60% by weight or more. In some other embodiments, the proportion of the azo polymerization initiator to the total thermal polymerization initiator is, for example, about 65% by weight or more, 75% by weight or more, 85% by weight or more, 95% by weight or more, or 99% by weight or more. In addition, the upper limit of the proportion of the azo polymerization initiator to the total thermal polymerization initiator is 100% by weight, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less.

[0138] In addition, in some preferred embodiments, the adhesive layer includes a peroxide-based polymerization initiator as a thermal polymerization initiator. Thus, by utilizing the high initiation efficiency of the peroxide-based polymerization initiator (specifically, an organic peroxide-based polymerization initiator), even when the amount of the multifunctional monomer used is relatively small, there is also a tendency to fully thermally cure and easily achieve easy peeling by heating. In some embodiments, it is appropriate that the ratio of the thermal polymerization initiator as a whole contained in the adhesive layer by the peroxide-based polymerization initiator is set to about 10% by weight or more. From the perspective of effectively exerting the effect of the peroxide-based polymerization initiator, it is preferably more than 30% by weight, more preferably more than 40% by weight, and further preferably more than 50% by weight (for example, more than 50% by weight), can be more than 55% by weight, or can be more than 60% by weight. In some other embodiments, the ratio of the peroxide-based polymerization initiator to the above-mentioned thermal polymerization initiator as a whole is, for example, about 65% by weight or more, can be more than 75% by weight, can be more than 85% by weight, can be more than 95% by weight, or can be more than 99% by weight. The upper limit of the ratio of the peroxide-based polymerization initiator to the total thermal polymerization initiator is 100 wt %, and may be, for example, 90 wt % or less, 80 wt % or less, 70 wt % or less, or 60 wt % or less.

[0139] The total amount of thermal polymerization initiators contained in the adhesive layer (when containing more than two kinds, the total content of more than two kinds) is not particularly limited and can be set in a manner to achieve easy peeling by heating. In some embodiments, the total amount of the above-mentioned thermal polymerization initiators is, for example, 0.1 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive layer. By including the above-mentioned amount of thermal polymerization initiators in the adhesive layer, the thermal polymerization initiator and the multifunctional monomer are fully in contact in the adhesive, so that the reaction of the two can proceed rapidly and can have easy peeling by heating. From the viewpoint of easy peeling by heating, the total amount of thermal polymerization initiators relative to 100 parts by weight of the above-mentioned polymer is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and can also be 0.5 parts by weight or more. The upper limit of the total amount of the thermal polymerization initiator in the adhesive layer is not particularly limited. In some embodiments, the total amount of the thermal polymerization initiator relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) is, for example, less than 3 parts by weight, which is appropriate, preferably less than 2.5 parts by weight, more preferably less than 2.0 parts by weight, further preferably less than 1.5 parts by weight, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.9 parts by weight, can be less than 0.8 parts by weight, can be less than 0.7 parts by weight, and can also be less than 0.6 parts by weight. By setting the total amount of the thermal polymerization initiator within the specified range, it is possible to obtain adhesive properties such as adhesion, storage stability, and ideally achieve efficient thermosetting and easy peeling by heating. In addition, by limiting the amount of the thermal polymerization initiator used, it is possible to suppress the generation of released gas from the thermal polymerization initiator.

[0140] The content of the thermal polymerization initiator in the adhesive layer can also be determined by the relative relationship with the multifunctional monomer. In some ways, from the viewpoint of the probability of contact with the multifunctional monomer, it is appropriate to set the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 0.1 parts by weight or more, preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and also 0.5 parts by weight or more. In some ways, the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer is, for example, about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.9 parts by weight, can be less than 0.8 parts by weight, can be less than 0.7 parts by weight, and can also be less than 0.6 parts by weight.

[0141] (Crosslinking agent)

[0142] In the adhesive composition used for the formation of the adhesive layer, a crosslinking agent can be contained as required, mainly for the purpose of crosslinking in the adhesive layer or crosslinking of the adhesive layer and its adjacent surface. The crosslinking agent is typically contained in the adhesive layer in the form after the crosslinking reaction. Through the use of the crosslinking agent, the cohesive force of the adhesive layer can be appropriately adjusted.

[0143] The kind of cross-linking agent is not particularly limited, and can be selected from the cross-linking agent known in the past, for example, according to the composition of adhesive, in the adhesive layer, the cross-linking agent plays a suitable cross-linking function. As usable cross-linking agent, isocyanate cross-linking agent, epoxy cross-linking agent, oxazoline cross-linking agent, aziridine cross-linking agent, carbodiimide cross-linking agent, melamine cross-linking agent, urea cross-linking agent, metal alkoxide cross-linking agent, metal chelate cross-linking agent, metal salt cross-linking agent, hydrazine cross-linking agent, amine cross-linking agent etc. can be exemplified. They can be used alone or in combination of two or more. From the viewpoint of realizing adhesion and cohesion well at the same time, preferably isocyanate cross-linking agent, epoxy cross-linking agent, oxazoline cross-linking agent, aziridine cross-linking agent, carbodiimide cross-linking agent, particularly preferably isocyanate cross-linking agent.

[0144] As the isocyanate crosslinking agent, a polyfunctional isocyanate compound having two or more functions can be used. For example, aromatic isocyanates such as toluene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatephenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as hexamethylene diisocyanate; and the like can be cited. Examples of commercially available products include isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate L”), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate HL”), isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name “Coronate HX”), and trimethylolpropane / xylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “Takenate D-110N”).

[0145] As the epoxy crosslinking agent, a substance having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl meta-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical, trade name "EPICLON CR-5L" manufactured by DIC, trade name "Denacol EX-512" manufactured by Nagase Chemtex, trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd., and the like.

[0146] As the oxazoline crosslinking agent, any oxazoline crosslinking agent having one or more oxazoline groups in one molecule can be used without particular limitation.

[0147] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(1-(2-methyl)aziridinyl propionate)].

[0148] As the carbodiimide-based crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.

[0149] The amount used when a cross-linking agent is used (the total amount thereof when two or more cross-linking agents are used) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as bonding force and cohesive force in a well-balanced manner, the amount of the cross-linking agent used is an amount greater than 0 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive layer. The amount of the cross-linking agent used can be, for example, 0.001 parts by weight or more, 0.01 parts by weight or more, 0.1 parts by weight or more, or 0.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. In some embodiments, the amount of the cross-linking agent used is, for example, 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, or 2.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. The upper limit of the amount of cross-linking agent used is not particularly limited. It is appropriate to set it to about 20 parts by weight or less relative to 100 parts by weight of the above-mentioned polymer (specifically, the base polymer, such as an acrylic polymer). In some embodiments, it is preferably 10 parts by weight or less, and can be 7 parts by weight or less, or 5 parts by weight or less.

[0150] In order to more effectively carry out the cross-linking reaction, a cross-linking catalyst can be used. As the cross-linking catalyst, metal cross-linking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, triacetylacetonate iron, butyl tin oxide, dioctyltin dilaurate, etc. are exemplified. The amount of the cross-linking catalyst used is not particularly limited. The amount of the cross-linking catalyst used relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive layer can be set to, for example, about 0.0001 parts by weight or more, about 0.001 parts by weight or more, or about 0.005 parts by weight or more, and in addition, it can be set to about 1 part by weight or less, about 0.1 parts by weight or less, or about 0.05 parts by weight or less.

[0151] The adhesive composition used for forming the adhesive layer can contain a compound that produces keto-enol tautomerism as a crosslinking retarder as desired. For example, in an adhesive composition containing an isocyanate crosslinking agent or an adhesive composition that can be used in combination with an isocyanate crosslinking agent, a compound that produces keto-enol tautomerism can be preferably used. Thus, the effect of extending the pot life of the adhesive composition can be exerted.

[0152] As compounds that produce keto-enol tautomerism, various β-dicarbonyl compounds can be used. As specific examples, β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetic acid esters such as methyl acetoacetate and ethyl acetoacetate; propionylacetic acid esters such as ethyl propionylacetate; isobutyrylacetic acid esters such as ethyl isobutyrylacetate; malonates such as methyl malonate and ethyl malonate; and the like. Among them, acetylacetone and acetoacetic acid esters can be cited as suitable compounds. The compound that produces keto-enol tautomerism can be used alone or in combination of two or more.

[0153] The amount of the compound that produces keto-enol tautomerism used can be, for example, from 0.1 part by weight to 20 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer, for example, an acrylic polymer) contained in the adhesive layer, and it is appropriate to set it to from 0.5 part by weight to 15 parts by weight. For example, it can be from 1 part by weight to 10 parts by weight, and it can also be from 1 part by weight to 5 parts by weight.

[0154] (Other ingredients)

[0155] The adhesive layer may contain various additives commonly used in the adhesive composition field such as adhesion imparting agents, silane coupling agents, peeling force modifiers (surfactants, etc.), viscosity modifiers (such as tackifiers), leveling agents, plasticizers, fillers, colorants such as pigments and dyes, stabilizers, preservatives, and anti-aging agents as needed. For such various additives, conventionally known additives can be used by conventional methods, and since the present invention is not particularly characterized, detailed description is omitted.

[0156] It should be noted that the technology disclosed herein can achieve desired adhesive properties such as adhesion without using an adhesion-imparting agent. In some embodiments, the content of the adhesion-imparting agent in the adhesive layer can be, for example, less than 10 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive layer, and can further be set to less than 5 parts by weight. The content of the above-mentioned adhesion-imparting agent can be less than 1 part by weight (for example, less than 0.5 parts by weight), and can also be less than 0.1 parts by weight (0 parts by weight or more and less than 0.1 parts by weight). The adhesive layer can be a material that does not contain an adhesion-imparting agent.

[0157] (Form of Adhesive Composition)

[0158] Although not particularly limited, the technology disclosed herein can be preferably implemented using a solvent-based adhesive composition. The above-mentioned solvent-based adhesive composition is an adhesive composition in the form of an adhesive-forming component contained in an organic solvent. The solvent-based adhesive composition typically contains a solution polymer of a monomer component, a multifunctional monomer, and optionally other additives. In the form of a solvent-based adhesive (layer), the effect brought about by the technology disclosed herein can be effectively exerted. The solvent contained in the solvent-based adhesive composition can be appropriately selected from conventionally known organic solvents. For example, any one solvent selected from the following, or a mixed solvent of two or more, can be used, namely: aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (for example, monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; and the like.

[0159] (Formation of Adhesive Layer)

[0160] The adhesive layer disclosed herein can be formed by a method known in the past. After the adhesive composition is imparted (e.g., applied) to a suitable surface, the adhesive can be formed in the form of a layer (adhesive layer) by appropriately implementing a curing treatment. The curing means (e.g., drying, crosslinking, polymerization, cooling, etc.) of the adhesive composition can be only applicable to one, or more than two can be applicable simultaneously or in multiple stages. In a solvent-based adhesive composition, typically, the composition can be dried (preferably further crosslinked) to form an adhesive.

[0161] For example, in the case of the two-sided adhesive sheet without substrate, after the adhesive composition is given to the surface (peel-off surface) with releasability, the method for forming adhesive layer on the surface by making this adhesive composition solidify. In the case of the adhesive sheet with substrate, the method (direct method) can be adopted by directly giving (typically coating) adhesive composition to this substrate and solidifying it to form adhesive layer. In addition, it is also possible to adopt the method (transfer method) by giving adhesive composition to the surface (peel-off surface) with releasability and solidifying it and forming adhesive layer on the surface, and this adhesive layer is transferred to substrate. As the above-mentioned peel-off surface, the surface of the release liner, the back side of the substrate through peeling treatment, etc. can be utilized. It should be noted that the adhesive layer disclosed here is typically formed continuously, but is not limited to such form, for example, can also be formed as the adhesive layer of regular or random patterns such as dot-shaped, strip-shaped.

[0162] The adhesive composition can be applied by using a known or commonly used coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a die coater, a rod coater, an air knife coater, or a spray coater. Alternatively, the adhesive composition can be applied by impregnation, curtain coating, or the like.

[0163] From the viewpoints of promoting the cross-linking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature is not particularly limited, for example, it can be set to about 40 to 100°C, and is generally preferably set to about 60 to 80°C. For example, the heating temperature of the drying at the above temperature (for example, about 1 to 10 minutes, more specifically about 3 to 7 minutes) is low, and sometimes the volatilization of the solvent is also in progress. In the adhesive composition containing a multifunctional monomer and a thermal polymerization initiator, the reaction of the multifunctional monomer and the deactivation of the thermal polymerization initiator are negligible. In addition, after the adhesive composition is dried, it can be aged for the purpose of adjusting the transfer of components in the adhesive layer, carrying out the cross-linking reaction, and relaxing the strain that may exist in the substrate and the adhesive layer.

[0164] (thickness)

[0165] The thickness of the adhesive layer is not particularly limited. The thickness of the adhesive layer is usually more than 1 μm, can be more than 2 μm, or can be more than 3 μm. There is a tendency that the greater the thickness of the adhesive layer, the higher the adhesion to the adherend. In some preferred embodiments, the thickness of the adhesive layer is more than 5 μm, can be more than 7 μm, or can be more than 9 μm. It is appropriate to set the upper limit of the thickness of the adhesive layer to about 200 μm or less, for example, it can be less than 100 μm (for example, less than 100 μm), or it can be less than 50 μm. By limiting the thickness of the adhesive layer within a specified range, the residual adhesive caused by cohesive failure is prevented from being generated, and there is a tendency to easily obtain easy peelability. In addition, a thin adhesive layer is advantageous in terms of thinning of the adhesive sheet, and there is a tendency to be excellent in the followability of the adherend. In addition, by adopting a thin adhesive layer, the amount of released gas from the adhesive layer can be reduced. In some preferred embodiments, the thickness of the adhesive layer is 40 μm or less, may be 30 μm or less (eg, less than 30 μm), may be 20 μm or less, or may be 15 μm or less.

[0166] <Base material layer>

[0167] The adhesive sheet disclosed herein may include a substrate layer. As a substrate (layer) supporting (lining) the adhesive layer, various sheet-like substrates can be used. As the above-mentioned substrate, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of resin films, polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers can be cited; polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); vinyl chloride resin film; vinyl acetate resin film; polyamide resin film; fluororesin film; cellophane; etc. As other examples of resin films, resin films formed by one or more engineering plastics (which may be super engineering plastics) in polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylate resins, polyamideimide resins, and polyimide resins can be cited. The use of engineering plastics is preferred from the viewpoint of heat resistance. Examples of paper include Japanese paper, kraft paper, glassine, woodfree paper, synthetic paper, coated paper, etc. Examples of cloth include woven fabrics or nonwoven fabrics obtained by spinning various fibrous materials alone or in a blended manner. Examples of the above-mentioned fibrous materials include cotton, staple fibers, Manila hemp, pulp, rayon, acetate fibers, polyester fibers, polyvinyl alcohol fibers, polyamide fibers, polyolefin fibers, etc. Examples of rubber sheets include natural rubber sheets, butyl rubber sheets, etc. Examples of foam sheets include foamed polyurethane sheets, foamed polychloroprene rubber sheets, etc. Examples of metal foils include aluminum foil, copper foil, etc.

[0168] In some preferred embodiments, a resin film having a specified rigidity (strength) and excellent processability and usability is used as a substrate (layer). Among them, a polyester film is preferably used as the resin film substrate. It should be noted that in this specification, the so-called "resin film" is typically a non-porous film, and typically refers to a resin film that is substantially free of bubbles (voids). Therefore, the above-mentioned resin film is a concept that is different from foam film and non-woven fabric. The density of the resin film that can be used as a substrate can be about 0.85 to 1.50 g / cm 3 (e.g. 0.90 g / cm 3 ~1.20g / cm 3 , typically 0.92 g / cm 3 ~1.05g / cm 3 The resin film may be a single-layer structure or a multi-layer structure with two or more layers (eg, a three-layer structure).

[0169] The substrate layer (e.g., resin film) may be mixed with known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, antiblocking agents, etc. as needed. The amount of the additives is not particularly limited and can be appropriately set according to the application, etc.

[0170] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.

[0171] The substrate layer may be substantially composed of a resin film. Alternatively, the substrate layer may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printing layer for imparting a desired appearance, a laminating layer, an antistatic layer, a primer layer, a peeling layer, and other surface treatment layers.

[0172] The thickness of the substrate layer is not particularly limited, and can be appropriately selected according to the purpose, and can generally be 1 to 500 μm. From the viewpoints of processability, usability, operability, etc., it is appropriate that the thickness of the substrate layer is 2 μm or more (e.g., 3 μm or more, typically 5 μm or more), can be about 7 μm or more, or can be 10 μm or more. In addition, it is appropriate that the thickness of the substrate layer is about 200 μm or less, and from the viewpoint of lightweight and thin thickness, it is preferably about 100 μm or less, more preferably about 50 μm or less, can be 30 μm or less, can be 20 μm or less, or can be 15 μm or less. When the thickness of the substrate layer becomes smaller, there is a tendency to improve the softness of the adhesive sheet and the followability of the surface shape of the adherend.

[0173] The adhesive layer side surface of the substrate layer can be subjected to corona treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, coating of primer (primer) and other previously known surface treatments as needed. Such surface treatment can be used to improve the adhesion between the substrate layer and the adhesive layer, in other words, it can be used to improve the anchoring of the adhesive layer to the substrate layer. The composition of the primer is not particularly limited and can be appropriately selected from known substances. The thickness of the primer layer is not particularly limited, for example, about 0.01 μm to 1 μm is appropriate, preferably about 0.1 μm to 1 μm. In addition, the back of the substrate layer can be subjected to the above-mentioned various surface treatments, antistatic treatment and other surface treatments.

[0174] <Total thickness>

[0175] The total thickness of the adhesive sheet disclosed herein (which may include an adhesive layer and a substrate layer, but does not contain a release liner) is not particularly limited, and it is appropriate to set it in the range of about 5 to 1000 μm. From the perspectives of adhesive properties and usability, the total thickness of the adhesive sheet can be more than 10 μm, more than 15 μm, or more than 20 μm. In addition, from the perspective of lightweight and thin thickness, in some embodiments, the total thickness of the adhesive sheet is less than 500 μm, or less than 300 μm. In some preferred embodiments, the total thickness of the adhesive sheet is less than 100 μm (for example, less than 100 μm), more preferably less than 50 μm, or less than 30 μm. Reducing the thickness of the adhesive sheet is also advantageous in terms of filmization, miniaturization, lightweighting, and resource saving.

[0176] <Release liner>

[0177] The release liner used for the adhesive sheet disclosed herein is not particularly limited, and for example, a release liner having a release treatment on the surface of a liner substrate such as a resin film or paper, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. In the above-mentioned release treatment, for example, a release treatment agent such as a silicone-based or long-chain alkyl-based release agent can be used. In some embodiments, a release-treated resin film can be preferably used as the release liner.

[0178] <Peeling method>

[0179] According to the present specification, a method for peeling an adhesive sheet adhered to an adherend from the adherend is provided. The above-mentioned peeling method includes: after the above-mentioned adherend to which the adhesive sheet is adhered is subjected to a heat treatment at a temperature higher than 150°C, the step of peeling the adhesive sheet from the adherend. The adhesive sheet disclosed herein has heat-resistant peelability, so it can be easily peeled from the adherend even after being exposed to heating exceeding 150°C. In addition, as far as the adhesive sheet is concerned, since the released gas from the adhesive layer is reduced, it is preferably suitable for use in which the released gas is not expected, and the heat-resistant peelability (heat-resistant peelability) can be exerted.

[0180] The temperature of the heat treatment of the adherend to which the adhesive sheet is attached can be above 160°C, or above 170°C. The upper limit of the heat treatment temperature may vary depending on the purpose of the heat treatment, the heat resistance of the adherend, etc., but is generally below 250°C, and may be below 230°C or below 200°C. The time of the heat treatment is not particularly limited, and may be above 3 minutes, above 5 minutes, above 7 minutes, or above 9 minutes. In addition, from the perspective of the efficiency of the heating process, the heat treatment time may be within 1 hour, within 30 minutes, within 15 minutes, or within 10 minutes. The adhesive sheet disclosed herein is heat-cured by the above-mentioned short-time high-temperature heat treatment to thermally cure the adhesive, and can show easy peeling by heating. In addition, in some embodiments, the heat treatment time may be above 10 minutes, above 30 minutes, above 60 minutes, more than 1 hour, more than 3 hours, more than 4 hours, or more than 5 hours. For the adhesive sheet disclosed herein, the adhesive is thermally cured by the above-mentioned high temperature heating treatment, the peeling force is reduced, or the rise of the peeling force is suppressed, and even if the heated state continues for a long time, the rise of the peeling force (heavy peeling) will not occur or be suppressed. Therefore, the heating easy peelability (heat-resistant easy peelability) can be maintained after a long heating treatment. The upper limit of the heating treatment time is not particularly limited, but from the viewpoint of the efficiency of the heating process, it can be within 10 hours, within 5 hours, or within 3 hours.

[0181] In addition, some preferred embodiments of the adhesive sheet may be an adhesive sheet having the desired adhesive properties even if it is stored for a specified period before being attached to the adherend. The above-mentioned adhesive sheet has good storage stability, so even if it is exposed to a temperature of 40°C or above (e.g., 40°C or above and below 100°C), and further exposed to a temperature of 50°C or above or 60°C or above during storage, the desired adhesive properties and heat-peelability can be maintained. In addition, even in an environment below 40°C, for example, in the case of long-term storage for more than 30 days, more than 100 days, or even half a year or more than a year, changes will occur in the adhesive properties originally designed. In particular, with respect to adhesives having heat-peelability, there is a risk that the heat-polymerization initiator will decompose and the desired heat-peelability will be damaged due to long-term storage for adhesives containing thermal polymerization initiators, but the above-mentioned adhesive sheet has heat-peelability and good storage stability, so regardless of long-term storage, temperature conditions during storage, etc., it can also exert heat-peelability after storage, and has high utilization value.

[0182] <Application>

[0183] The adhesive sheet disclosed herein has heat-removable properties, so it can be used as an adhesive sheet for various purposes requiring heat-removable properties, such as the use of peeling and removing from the adherend by heating. For example, in the state of being attached to the adherend, it can be preferably used for purposes that can be exposed to heating exceeding 150°C (exceeding 150°C and about 250°C or less, for example, above 160°C, and further above 170°C). As such uses, for example, masking uses, temporary fixing uses, and protective uses that require heat resistance for the adhesive sheet can be cited. In addition, for example, it can also be preferably used as a process material fixed to the adherend and peeled off in the manufacturing process of electronic equipment and electronic components. In addition, as a suitable use of the adhesive sheet disclosed herein, semiconductor element manufacturing purposes can be cited. For example, in semiconductor wafer processing (typically silicon wafer processing), it can be preferably used as a wafer fixing sheet for fixing the wafer to a fixing plate. In addition, the adhesive sheet disclosed herein can also be preferably used as a protective sheet for protecting the wafer in the above-mentioned wafer processing. In particular, when semiconductor elements are manufactured, they are exposed to heating during processing steps, etc., so it is preferred to use an adhesive sheet with heat resistance and easy peelability. In addition, the adhesive sheet disclosed herein can also be applied to optical uses that require heat resistance. More specifically, for example, as an optical adhesive sheet for use in bonding optical components (optical component bonding), for the manufacture of products (optical products) using the above-mentioned optical components, the adhesive sheet disclosed herein can be used. It should be noted that the above-mentioned optical component refers to a component having optical properties (for example, polarization, light refraction, light scattering, light reflectivity, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.).

[0184] In addition, the release gas of the adhesive sheet disclosed herein is reduced, so it can be preferably used for various purposes where the release gas is not expected. For example, if the release gas component from the adhesive sheet is large, the adherend is contaminated due to the release gas component, which can be the cause of undesirable conditions such as poor appearance. Therefore, in the use exposed to the above-mentioned heating, it is desirable to suppress the amount of released gas from the adhesive sheet. In addition, for example, in the use of using pressure difference to temporarily fix materials, the use of adhesion of adhesive sheets, and the use of processing adherends under vacuum, the adhesive sheet is used in a vacuum or reduced pressure environment. In these uses, if the release gas amount from the adhesive sheet is large, the vacuum degree is reduced, which can be the cause of undesirable conditions. The adhesive sheet disclosed herein can be used for various uses including the above-mentioned use of undesirable release gas with less restrictions.

[0185] The type of material (adherend material) disclosed herein for pasting is not particularly limited. The adhesive sheet disclosed herein can be used for fixing and protecting various components and materials. As examples of adherend materials, for example, it can be: glasses such as alkaline glass and alkali-free glass; metal materials such as stainless steel (SUS) and aluminum; ceramic materials such as alumina and silica; resin materials such as polyester resins such as PET, acrylic resins, ABS resins, polycarbonate resins, polystyrene resins, and transparent polyimide resins; and so on. As suitable examples of adherend materials, for example, glass materials such as alkaline glass, semiconductor chips, etc. can be cited. The above-mentioned glass material can be, for example, a glass plate having a surface with a transparent conductive film (such as ITO (indium tin oxide) film) and FPC (flexible circuit board) that can be used for tablet personal computers, mobile phones, organic LEDs (light emitting diodes), etc.

[0186] The matters disclosed in this specification include the following.

[0187] [1] An adhesive sheet having an adhesive layer, wherein:

[0188] The adhesive layer comprises a polymer and a multifunctional monomer having a weight loss rate of 1% or less at 180°C in a thermogravimetric analysis (TGA) under a temperature increase condition of 10°C / min,

[0189] The content of the polyfunctional monomer is 30 parts by weight or more relative to 100 parts by weight of the polymer.

[0190] The adhesive sheet has a post-heat peel strength to a glass plate measured after heating at 180° C. for 1 hour of 1.0 N / 20 mm or less.

[0191] [2] The pressure-sensitive adhesive sheet according to [1] above, wherein the molecular weight of the polyfunctional monomer is 250 or more.

[0192] [3] The pressure-sensitive adhesive sheet according to [1] or [2] above, wherein the polyfunctional monomer has four or more ethylenically unsaturated groups.

[0193] [4] The pressure-sensitive adhesive sheet according to any one of [1] to [3] above, comprising a polyfunctional acrylate monomer as the polyfunctional monomer.

[0194] [5] The pressure-sensitive adhesive sheet according to any one of [1] to [4] above, comprising an acrylic polymer as the polymer.

[0195] [6] The pressure-sensitive adhesive sheet according to any one of [1] to [5] above, wherein the pressure-sensitive adhesive layer further contains a thermal polymerization initiator.

[0196] [7] The pressure-sensitive adhesive sheet according to [6] above, wherein the content of the thermal polymerization initiator in the pressure-sensitive adhesive layer is less than 1.2 parts by weight based on 100 parts by weight of the polymer.

[0197] [8] A peeling method, which is a method for peeling the pressure-sensitive adhesive sheet according to any one of [1] to [7] above, which is adhered to an adherend, the peeling method comprising:

[0198] A step of subjecting the adherend to which the pressure-sensitive adhesive sheet is attached to the adherend to a heat treatment at a temperature higher than 150° C., and then peeling the pressure-sensitive adhesive sheet from the adherend.

[0199] Example

[0200] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are based on weight.

[0201] <Evaluation of weight loss rate of multifunctional monomers upon heating at 180°C>

[0202] Before developing adhesive sheets, a polyfunctional monomer with high heat resistance was selected by TGA. Specifically, as multifunctional monomer materials, 1,6-hexanediol diacrylate (HDDA, manufactured by Osaka Organic Chemical Industry Co., Ltd., molecular weight 226.3, number of functional groups 2), trimethylolpropane triacrylate (TMPTA, manufactured by Osaka Organic Chemical Industry Co., Ltd., molecular weight 296.3, number of functional groups 3), dipentaerythritol hexaacrylate (DPHA, manufactured by Osaka Organic Chemical Industry Co., Ltd., molecular weight 578.6, number of functional groups 6) and ultraviolet curable urethane acrylate oligomer (product name "purple light UV-1700B", manufactured by Mitsubishi Chemical Corporation, molecular weight 2000, number of functional groups 10) were prepared, and the weight reduction rate [%] of each multifunctional monomer material when it reached 180°C was measured under the measurement conditions of temperature increase of 10°C / min, air atmosphere, and flow rate of 25 mL / min. The results are shown in Table 1.

[0203] [Table 1]

[0204] Table 1

[0205] Material Name Weight reduction at 180°C HDDA 10% TMPTA 1% DPHA 0.5% Purple light UV-1700B 0.4%

[0206] As shown in Table 1, it was shown that the weight loss rate upon heating at 180° C. differed depending on the type of the polyfunctional monomer. Based on the results, pressure-sensitive adhesive sheets were prepared and evaluated as follows using DPHA and HDDA as polyfunctional monomers.

[0207] <Example 1>

[0208] (Preparation of Adhesive Composition)

[0209] In a reaction container equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirring device, 85 parts of methoxyethyl acrylate (MEA), 10 parts of N-vinyl-2-pyrrolidone (NVP), 5 parts of 4-hydroxybutyl acrylate (4HBA) and 0.5 parts of acrylic acid (AA) as monomer components, 300 parts of ethyl acetate as a polymerization solvent, and 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and a polymerization reaction (solution polymerization) was carried out at 61° C. for 6 hours under a nitrogen atmosphere, thereby obtaining a solution containing an acrylic polymer.

[0210] To the toluene solution of the acrylic polymer, 30 parts of DPHA as a multifunctional monomer, 3 parts of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, product name "Takenate D-101E"), and 0.5 parts of benzoyl peroxide (manufactured by NOF Corporation, product name "NYPER BMT 40SV", 10-hour half-life temperature: 73°C) as a thermal polymerization initiator were added relative to 100 parts of the acrylic polymer, and the mixture was uniformly mixed to prepare the solvent-based adhesive composition involved in this example.

[0211] (Production of Adhesive Sheet)

[0212] The adhesive composition obtained in the above manner was applied to the release surface of a commercially available PET release liner and dried at 80°C for 5 minutes to form an adhesive layer with a thickness of 10 μm. A PET film with a thickness of 12 μm was attached to the adhesive layer to prepare the adhesive sheet (single-sided adhesive sheet with a substrate) involved in this example. The adhesive surface of the above-mentioned adhesive sheet was protected by the release liner.

[0213] <Examples 2 to 5 and Comparative Examples 1 and 2>

[0214] The adhesive compositions of each example were prepared by the same method as in Example 1 except that the type and amount of the multifunctional monomer and the type of the thermal polymerization initiator were changed as shown in Table 2, and the single-sided adhesive sheet with a substrate of each example was prepared by using the obtained adhesive composition in the same manner as in Example 1. It should be noted that in Table 2, the azo polymerization initiator refers to the product name "VAm-110" (2,2'-azobis(N-butyl-2-methylpropionamide), 10-hour half-life temperature: 110°C) manufactured by FUJIFILM Wako Pure Chemical Corporation.

[0215] <Evaluation>

[0216] (Initial peel strength F0)

[0217] The adhesive sheet is cut into a size of 20mm in width and 100mm in length. Under the environment of 23°C and 50%RH, a 2kg roller is reciprocated once to press the adhesive surface of the adhesive sheet and make it adhere to the alkaline glass plate (made by Matsunami Glass Industry Co., Ltd., with a thickness of 1.35mm and a blue plate edge grinding product) as the adherend. Under the same environment, the alkaline glass plate with the above-mentioned adhesive sheet is left to stand for 6 hours and used as an evaluation sample. The above-mentioned evaluation sample is set in a tensile testing machine under the environment of 23°C and 50%RH, and the peel strength (initial peel strength) F0 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / minute is measured. As a tensile testing machine, the product name "EZ-S 500N" made by Shimadzu Company or its equivalent can be used. In addition, when the evaluation object is a double-sided adhesive sheet, the non-measurement surface can be lined with a PET film to implement the measurement.

[0218] (Peel strength after heating F1)

[0219] Using an adhesive sheet, an evaluation sample is prepared by the method described in the above-mentioned determination of the initial peel strength F0. The obtained evaluation sample is heat-treated in an oven at 180°C for 1 hour, taken out of the oven, and allowed to stand for 30 minutes under an environment of 23°C and 50% RH. Then, the above-mentioned evaluation sample is set in a tensile testing machine under the same environment, and the peel strength (peel strength after heating) F1 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. Regarding the adherend, the tensile testing machine, and other matters, it is the same as the determination of the initial peel strength F0.

[0220] (Total amount of released gas when kept at 180℃ for 1 hour)

[0221] The adhesive sheet was used as a measurement sample, and the released gas was analyzed by gas chromatography-mass spectrometry (GC / MS) when it was kept at 180°C for 1 hour, and the total amount of released gas when it was kept at 180°C for 1 hour was quantified. 2 Or about 3 mg of the measurement sample. The specific measurement conditions are as follows.

[0222] (Analysis device)

[0223] Heating device: GERSTEL, TDU2

[0224] GC / MS: Agilent Technologies, 8890 / 5977B

[0225] (Measurement conditions)

[0226] TDU conditions (sample): 30℃(1min)→720℃ / min→180℃(60min)

[0227] TDU conditions (standard product): 30℃(1min)→720℃ / min→300℃(5min)

[0228] CIS conditions: -150℃(2.5min)→12℃ / sec→300℃(10min)

[0229] GC / MS conditions

[0230] Chromatographic column: HP-Ultra1( df=0.33μm)

[0231] Column temperature: 40℃(5min)→10℃ / min→100℃→20℃ / min→300℃(9min)

[0232] Column pressure: Constant flow mode (113kPa, Vac)

[0233] Column flow rate: 1mL / min (He)

[0234] Injection method: CIS, Split (20:1)

[0235] Detector: MS

[0236] Ion source temperature: 230°C

[0237] Ionization method: EI (70eV)

[0238] Table 2 shows the summary and evaluation results of each example.

[0239] [Table 2]

[0240]

[0241] As shown in Table 2, the adhesive sheets involved in Examples 1 to 5 have an adhesive layer containing more than 30 parts of a multifunctional monomer with a weight loss rate of less than 1% at 180°C relative to 100 parts of the polymer, and the peel strength F1 after heating at 180°C for 1 hour is less than 1.0N / 20mm, which has easy peelability by heating, and the released gas when heated at 180°C for 1 hour is less than 1000μg per 1g of the adhesive sheet. On the other hand, in Comparative Example 1 using an adhesive containing less than 30 parts of a multifunctional monomer relative to 100 parts of the polymer, the peel strength F1 after heating becomes high and the easy peelability by heating is deteriorated. It is believed that the reason is that due to the insufficient amount of the multifunctional monomer, the adhesive does not cure quickly during the heating treatment, and heavy peeling occurs. In addition, in Comparative Example 2 using a multifunctional monomer with a weight loss rate of more than 1% at 180°C as a multifunctional monomer, the released gas when heated at 180°C for 1 hour becomes a high value of 165000μg / g. From the above results, it can be seen that according to the following adhesive sheet, it is possible to achieve easy heat peelability and reduced gas release, the adhesive sheet having an adhesive layer containing 30 parts by weight or more of a multifunctional monomer having a heating weight loss rate of less than 1% based on TGA at 180°C relative to 100 parts by weight of the polymer, and the peel strength after heating at 180°C for 1 hour is less than 1.0N / 20mm.

[0242] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes examples obtained by variously modifying and changing the specific examples described above.

[0243] Description of Reference Numerals

[0244] 1 Adhesive sheet

[0245] 1A Bonding surface

[0246] 1B Back

[0247] 10 base material layer

[0248] 10A One side surface

[0249] 10B The other side of the face

[0250] 20 adhesive layers

[0251] 20A bonding surface

[0252] 30 Release Liner

[0253] 50 Adhesive sheet with release liner

Claims

1. An adhesive sheet having an adhesive layer, wherein: The adhesive layer comprises a polymer and a multifunctional monomer having a weight loss rate of 1% or less at 180° C. in a thermogravimetric analysis (TGA) under a temperature increase condition of 10° C. / min, The content of the multifunctional monomer is 30 parts by weight or more relative to 100 parts by weight of the polymer. The adhesive sheet has a post-heating peel strength to a glass plate measured after heating at 180° C. for 1 hour of 1.0 N / 20 mm or less.

2. The adhesive sheet according to claim 1, wherein The molecular weight of the multifunctional monomer is 250 or more.

3. The adhesive sheet according to claim 1 or 2, wherein The multifunctional monomer has four or more ethylenically unsaturated groups.

4. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer includes a multifunctional acrylate-based monomer as the multifunctional monomer. 5 . The pressure-sensitive adhesive sheet according to claim 1 , comprising an acrylic polymer as the polymer.

6. The adhesive sheet according to claim 1 or 2, wherein The adhesive layer further includes a thermal polymerization initiator.

7. The adhesive sheet according to claim 6, wherein The content of the thermal polymerization initiator in the adhesive layer is less than 1.2 parts by weight based on 100 parts by weight of the polymer.

8. A peeling method, which is a peeling method of the pressure-sensitive adhesive sheet according to claim 1 or 2 adhered to an adherend, the peeling method comprising: A step of subjecting the adherend to which the pressure-sensitive adhesive sheet is attached to the adherend to a heat treatment at a temperature higher than 150° C., and then peeling the pressure-sensitive adhesive sheet from the adherend.

Citation Information

Patent Citations

  • Sheet for fixing semiconductor wafer and chip pick-up method

    JP1998209087A

  • Wafer processing method

    JP2015029105A

  • Thermosetting adhesive composition for adhesive sheet for protecting chemical, adhesive for adhesive sheet for protecting chemical by crosslinking same, adhesive sheet for protecting chemical and application method of adhesive sheet for protecting chemical

    JP2016204617A

  • Double faced adhesive tape, and stacking body of thin film component and supporting component

    JP2019056101A

  • Information processing device, learning device, and control method for information processing device

    JP2022120902A